Efektivitas Situs Web lpmdinamika.co dalam Menyebarkan Informasi kepada Mahasiswa Kota Medan - Nurhanifah, Nurhanifah; Arrasyid, Muhammad Haritz (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
This study aims to analyze the effectiveness of lpmdinamika.co as an information delivery platform for students in Medan. The research employed a descriptive qualitative approach using in-depth interviews and content observation. Participants were selected from four universities in Medan: UIN SU, USU, Unimed, and UMSU. The findings reveal that lpmdinamika.co is considered effective in terms of accessibility, content consistency, and relevance. The website is utilized not only by UIN SU students but also by students from other universities, indicating its broad reach and inclusiveness. Additionally, keyword insights show high engagement with campus-related topics, student opinions, and academic content. Despite these strengths, the study also identifies several technical issues, such as inappropriate ads and occasional slow access, which may hinder user experience. These challenges highlight the importance of regular website maintenance and improvements in technical infrastructure. Overall, lpmdinamika.co fulfills its function as a digital campus media platform that meets student information needs, yet continuous enhancement is essential to maintain its reliability and effectiveness.